Model Kebijakan Komunitas Kampung Membangun: Studi Evaluasi Pengelolaan Dana Kampung Berbasis Para-Para Adat di Kota Jayapura - Saru, Rustan; Silo, Akbar; Kadir, Akhmad (JURNAL EKOLOGI BIROKRASI, 2022)
The Village Fund program aims to carry out development from below, which began in the village government skup in accordance with the mandate of PP No. 58 of 2005. Therefore, the Community and Village Empowerment Office (DPMK) of Jayapura City, has organized village financial activities. The regulation of village fund management in Jayapura City is regulated through three Jayapura Mayoral Regulations. The purpose of this research is to evaluate the governance of village funds, then to be the formulation of an effective village fund management model. Qualitative research type with applied social approach. Research locations include districts in Jayapura City. The primary data source comes from observations and interviews. Data collection techniques use direct observation techniques and in-depth interviews. Data analysis includes data collection, data reduction, presentation, and inference. Data validity test is done by triangulation. The results showed that the management of village funds in Jayapura City is constrained by the lack of public understanding about village funds accompanied by the quality of human resources managers are not yet skilled. The model of village fund management developed by the involvement of indigenous peoples as a representation of the implementation of government based on local wisdom in order to be used as social capital to build community participation. Access to indigenous peoples should also be limited to aspects of supervision in the management and involvement in the formulation of programs for the use of village budgets that are more focused on organizing programs for the common good.